Airborne fungal exposure and nasal deposition among workers in biomass-based energy production - Victor Carp Kofoed; Hassan Al-Saidi; Jeppe Lund Nielsen; Anne Mette Madsen (Aerobiologia, 2026)
The growing demand for sustainable energy alternatives has substantially increased employment in biomass-based energy production. However, solid biomass, including wood and straw, can harbor fungi that become airborne during handling and processing. Thus, workers may face elevated inhalation exposure to fungal bioaerosols with potential implications for respiratory health. This study aimed to characterize the airborne fungal exposure and nasal deposition among workers in biomass-based energy production to support occupational risk evaluation of fungal bioaerosols. We measured 48 whole-workday personal exposures, and collected 36 nasal lavage (NAL) samples from workers at four facilities that combust straw, wood chips, or wood pellets. Fungi were quantified and identified to species level using MALDI-TOF MS; the aerodynamic diameter of fungal bioaerosols was measured using size-fractionated sampling; and Aspergillus fumigatus isolates were tested for azole resistance using broth microdilution. Fungal concentrations and species compositions differed significantly between biomass facilities in personal exposures and NAL samples. Airborne exposure was positively associated with nasal deposition, while the two sample types showed distinct species compositions. Risk group 2 fungi were abundant in workers’ exposures, and three Aspergillus fumigatus isolates recovered from the straw facility were resistant to itraconazole, voriconazole, and posaconazole. The findings indicate that the type of biomass affects workers’ fungal exposure and nasal deposition in terms of concentrations and species, and highlight additional concerns related to airway deposition and antifungal resistance. Finally, the study demonstrates the utility of NAL as a tool in exposure assessment.